MANIPULATIVE MOVEMENT SKILLS OF CHILDREN WITH INDEPENDENCE - Bulubaan, Addriana; Sardiman, Sardiman; Sianto, Moh Ifkhal; Bakar, Abu (JURNAL PENDIDIKAN GLASSER, 2023)
Manipulative skills are modified to create movement skills for students with special needs who are mentally disabled in SLB Huntap Palu. The aim of the research was to determine the manipulative movement skills of students with special needs who are mentally retarded at SLB Huntap Palu. The research methodology is a quantitative methodology with a descriptive analysis approach. Purposive sampling technique was used to select a sample of 12 students in the study, all of whom experienced mental disorders. This research testing includes a ball throwing test. Data analysis shows that: manipulative movement skills and ball throwing skills in mentally retarded children total 10, when included in the formula the result is 60%; Based on the score category guidelines, the ball throwing game for mentally retarded children is included in the high category. According to the standard score category, the ability to catch the ball in mentally retarded children is included in the high group. Deaf children have a ball catching ability level of 15, which if entered into the algorithm will give a result of 75%. The conclusion of the research is that the manipulative movement skills of children with special needs at SLB Huntap Palu are in the good category.